Nihilisme identitaire dans Lord of the Flies de William Golding et A Slight Ache de Harold Pinter - Maurice Gning (European Scientific Journal, ESJ, 2017)
Two works of the mid-twentieth-century British literature form the corpus of this study, namely Lord of the Flies (1954) by the English William Golding and A Slight Ache (1961) by his contemporary and compatriot Harold Pinter. Based on the issue of nihilism as defined by Nietzsche and on the poststructuralist theory of the death of the subject, it aims to analyze how the two postmodern writers, Golding and Pinter, stress the emptiness of the human identity resulting from the collapse of the Western culture. The analysis shows that, in order to reveal this identity vacuity, the two authors make use of strategies at first sight different, but that prove to be basically similar. This identity emptiness is beforehand expressed by the emptiness of the fiction space, the isolation of characters and the justified absence of traditional points of reference that could constitute the base of the societies they attempt to form. The predictable collapse of these societies discloses the strange face of the individual behind it, and unveils the kingdom of nothingness foregrounded, in both works, by the image of darkness and chaos.